A 121-ka record of Western Andean fluvial response to suborbital climate cycles recorded by rhythmic grain size variations of the Lima fluvial fan - (:unkn) unknown (John Wiley & Sons, Inc., 2024)
A complete, fluvial stratigraphic record for the last glacial period of the Western Andes in Peru is not available due to preservation issues and spatial variability in sedimentation. Deposits are typically restricted to incomplete records of fluvial ter...
Keywords: Cambio climático; Geomorfología fluvial